2012
DOI: 10.1073/pnas.1218633110
|View full text |Cite
|
Sign up to set email alerts
|

Rise to dominance of angiosperm pioneers in European Cretaceous environments

Abstract: The majority of environments are dominated by flowering plants today, but it is uncertain how this dominance originated. This increase in angiosperm diversity happened during the Cretaceous period (ca. 145-65 Ma) and led to replacement and often extinction of gymnosperms and ferns. We propose a scenario for the rise to dominance of the angiosperms from the Barremian (ca. 130 Ma) to the Campanian (ca. 84 Ma) based on the European megafossil plant record. These megafossil data demonstrate that angiosperms migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 53 publications
3
67
1
Order By: Relevance
“…However, recent studies have shown that extrinsic influences combined with biotic factors may drive species diversity at the multimillion-year time scale (6,12), reviving the potential role of global climate change (13,14) on angiosperm radiation. Such a combination is supported by fossil data, as illustrated by the latest studies based on the European megafossil plant record that provided a scenario in which angiosperm radiation was concomitant, in space and time, with the evolution of the physical environment (15).…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…However, recent studies have shown that extrinsic influences combined with biotic factors may drive species diversity at the multimillion-year time scale (6,12), reviving the potential role of global climate change (13,14) on angiosperm radiation. Such a combination is supported by fossil data, as illustrated by the latest studies based on the European megafossil plant record that provided a scenario in which angiosperm radiation was concomitant, in space and time, with the evolution of the physical environment (15).…”
mentioning
confidence: 73%
“…1C). This may involve the scenario inferred by Coiffard et al (15), with a migration in most of the continental surfaces in three phases, being globally relevant and not restricted to Europe. We favor an abiotic first-order context allowing angiosperm radiation by a global climate change driven by both a breakup of Pangea in Gondwana and Laurasia and the drift of the smaller land masses.…”
Section: Global Climate and Angiosperm Expansion And Diversificationmentioning
confidence: 90%
See 3 more Smart Citations